One Origen or two? The status quaestionis - Edwards, M (Routledge, 2015)
It has generally been assumed that there were two Origens in the early third century, both of whom were taught by Ammonius Saccas, the Alexandrian teacher of Plotinus. In recent years, it has become more common to maintain that there was only one Origen. Hermann Dörrie’s theory that there were two Origens, each taught by a different Ammonius, has enjoyed little favour, and some have denied the existence of the peripatetic Ammonius, proposed as a possible tutor for the Christian Origen. The first part of this article shows that the existence of two Ammonii is accepted by all scholars who are familiar with the evidence of Philostratus, Lives of the Sophists 2.27. The second points out that the identification of the two Origens raises chronological difficulties which are not always recognized in modern treatments of this question. The rest of the paper, responding to recent studies by Tobias Böhm and Ilaria Ramelli, argues that the teachings ascribed to “Origen” by later Neoplatonists are not sufficiently convergent with those of the Christian Origen to justify the conclusion that there was only one man of this name.